2022
DOI: 10.1029/2022gl099163
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Different Properties of Ionospheric Perturbations in the Vicinity of the Korean Peninsula After the Hunga‐Tonga Volcanic Eruption on 15 January 2022

Abstract: An explosive submarine volcanic eruption occurred at 04:15 universal time (UT) on 15 January 2022 at Hunga Tonga-Hunga Ha'apai (hereafter Hunga-Tonga) (Longitude 175.38°W, Latitude: 20.54°S). The volcanic explosivity index (VEI) of this event is estimated to be 5 or 6. This magnitude of eruption is comparable to the St. Helens volcano (VEI 5) in the United States on 18 May 1980 and the Pinatubo volcano (VEI 6) in the Philippines on 15 June 1991. The Hunga-Tonga event primarily draws attention from the aeronomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
1
8
0
3
Order By: Relevance
“…Among them, TIDs with velocities between 350 and 400 m/s had attracted extensive attention due to their strong amplitude (∼1.3 TECU). Whereas TIDs with velocities between 200 and 300 m/s were also observed globally (Hong et al, 2022;Matoza et al, 2022;Themens et al, 2022;Wright et al, 2022;Zhang et al, 2022). These slow TIDs are consistent with the third TID in our observation.…”
Section: Comparison With Previous Observationssupporting
confidence: 91%
See 1 more Smart Citation
“…Among them, TIDs with velocities between 350 and 400 m/s had attracted extensive attention due to their strong amplitude (∼1.3 TECU). Whereas TIDs with velocities between 200 and 300 m/s were also observed globally (Hong et al, 2022;Matoza et al, 2022;Themens et al, 2022;Wright et al, 2022;Zhang et al, 2022). These slow TIDs are consistent with the third TID in our observation.…”
Section: Comparison With Previous Observationssupporting
confidence: 91%
“…We used TEC data from a dense GNSS network in China to monitor the TIDs after the Tonga volcanic eruption. The main objectives and significance of our study can be summarized as follows: (a) After the event, the community investigated the global ionospheric response using multiple instruments in New Zealand, Australia, Japan, North America, and Western Europe (e.g., Aa et al., 2022; Harding et al., 2022; Hong et al., 2022; Lin et al., 2022; Matoza et al., 2022; Themens et al., 2022; Verhulst et al., 2022; Wright et al., 2022; Zhang et al., 2022). However, the dense Chinese GNSS data have not yet been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the extreme change in the thermospheric winds and the associated equatorial electric field disturbance, equatorial ionization anomalies (EIAs) were found to be suppressed and reshaped after the eruption (Aa, Zhang, Wang, et al, 2022;Gasque et al, 2022;Harding et al, 2022;Le et al, 2022). Significant equatorial plasma bubbles (EPBs) and irregularity activities were observed Hong et al, 2022;Sun et al, 2022), and the ionospheric disturbances in the conjugate hemisphere were also suggested (Lin et al, 2022). These and other studies (Astafyeva et al, 2022;Ghent & Crowell, 2022;K.…”
mentioning
confidence: 70%
“…Once the waves were generated in the atmosphere, wave signatures were observed propagating horizontally around the globe. The most persistent of these had properties consistent with a Lamb wave, a non‐dispersive pressure wave which propagated globally at speeds estimated between 300 and 390 m/s (with most estimates around 310 m/s), and whose signature was clearly distinguishable in total electron content (TEC) data taken by the Global Navigation Satellite System (Aa et al., 2022; Amores et al., 2022; Hong et al., 2022; Kataoka et al., 2022; Kulichkov et al., 2022; Lin et al., 2022; Otsuka, 2022; Wright et al., 2022; Zhang et al., 2022). Zhang et al.…”
Section: Introductionmentioning
confidence: 99%
“…• Extremely large ion drift velocities are observed ∼4,000 km from Tonga less than an hour post-eruption, before any atmospheric wave arrived • The ion drifts are driven by volcanically forced polarization electric fields transmitted along Earth's magnetic field via Alfvén waves • The drift signature is consistent with the dynamo effect of an expanding atmospheric wave with a >200 m/s amplitude Once the waves were generated in the atmosphere, wave signatures were observed propagating horizontally around the globe. The most persistent of these had properties consistent with a Lamb wave, a non-dispersive pressure wave which propagated globally at speeds estimated between 300 and 390 m/s (with most estimates around 310 m/s), and whose signature was clearly distinguishable in total electron content (TEC) data taken by the Global Navigation Satellite System (Aa et al, 2022;Amores et al, 2022;Hong et al, 2022;Kataoka et al, 2022;Kulichkov et al, 2022;Lin et al, 2022;Otsuka, 2022;Wright et al, 2022;Zhang et al, 2022). Zhang et al (2022) detected a TEC signature consistent with a propagating Lamb wave up to 100 hr after the eruption, after the wave had circled the globe at least three times.…”
mentioning
confidence: 99%